Profesionalisme Guru Dalam Implementasi Kolaborasi Kurikulum Pada Sekolah Dasar - Reky Lidyawati; Dian Maya Kurnia (Halaqa: Islamic Education Journal, 2019)
The aim of this research is to produce a new curriculum formulation that is better able to become an ideal curriculum for elementary school students who incidentally use the- matic learning and national exams using per subject. Research data obtained through documentation, observation sheets, and interview guidelines. The data obtained will be analyzed qualitatively. The output of this research is a curriculum collaboration model that is ready to use. The product of this research is expected to have a valid, practical, and effective nature. Then, the targeted TKT is TKT level 5. The results of this study are expected to make a theoretical contribution to the development of science in primary school education. The results of this study are also expected to have practical benefits for students and teachers at the elementary school level especially at SD Muhammadiyah 1 Panji, Situbondo district. The results of the study showed that in the planning stages of learning the teacher was still using the 2013 curriculum while in the implementation phase of learning the teacher had implemented 2 curricula, in the morning learning using the 2013 curriculum and in afternoon learning using the education unit level curriculum (KTSP).